Automobile Winter Roads in Transport System of Yakutia in Early 1930—1991 - A. A. Suleymanov (Научный диалог)
A historical analysis of the development of automobile winter roads in Yakutia, i.e. roads laid on frozen soil and surface ice of reservoirs, is presented. The chronological framework of the study covers the period from the moment the first of the winter roads appeared in the region in the early 1930s until the collapse of the Soviet Union. The study was carried out within the framework of the anthropology of cold, a direction of scientific research developed by the author and his colleagues, focused on identifying the significance of cryogenic processes and phenomena in the life of the population of the northern territories. Based on the involvement of a complex of archival materials, including those introduced into scientific circulation for the first time, the dynamics of the development of a network of automobile winter roads is traced. It has been established that the most important driver for the development of the transport system of Yakutia, including winter roads, in the period considered in the article was the interest in the development of deposits of various minerals — gold, tin, diamonds, etc. The place and role of automobile winter roads in the transport system of the region are revealed. The presented material indicates that winter roads were an important way to ensure the connectivity of the territory of Yakutia and one of the key tools to sustain the life support systems that have developed in the region.